Improvement of the Mechanical Properties of Biphasic Calcium Phosphate Ceramic Composite Using Silicene - ABDULRIDHA, Nazar J.; AL-GHABAN, Ahmed M.; AL-OBAIDI, Anwer J. (Engineering Transactions, 2023)
In light of recent events in the replacement and generation of human tissues, it is becoming extremely difficult to ignore the existence of bioceramics. Although hydroxyapatite and beta-tricalcium phosphate materials are frequently employed individually, they both lack certain qualities. As a result, combining hydroxyapatite and beta-tricalcium phosphate may result in the combination of their respective qualities. The current study aims to investigate the effect of using a novel nanostructure called silicene (silicon nanosheet-SiNS) on the mechanical properties of the composite ceramic (biphasic calcium p hosphate) at various ratios of hydroxyapatite and beta-tricalcium phosphate. The silicene has been synthesized and added at different weight percentages of 1, 3, and 5%. The results reveal that the compressive strength improved due to increasing the content of silicene. The average of increasing was between 58.6% and 142% because of the strong hexagonal structure of silicene. At the same time, the hardness of the biphasic calcium phosphate composite was enhanced by increasing the weight percentage of silicene. However, the hardness decreased when the content of silicene was more than 3% due to the presence of small cavities on the surface of the samples.